Community Service Program Based on Family Empowerment through Increased Knowledge on the Use of Local Food for Stunting Prevention - Lenny Gannika; Mulyadi Mulyadi; Jeanette Irene CH. Manoppo; Katrina Feby Lestari (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2026)
Stunting is a chronic nutritional problem that remains a public health challenge in Indonesia. Based on the 2023 Indonesian Health Survey, the national prevalence of stunting reached 21.5%, still above the national target of 14%. Preventing stunting requires a comprehensive approach through improving family nutrition literacy and optimizing the use of locally available food. This community service activity aims to analyze the effectiveness of family empowerment-based interventions in increasing knowledge about stunting prevention through education on the use of local Minahasa food. The activity used a quasi-experimental design with a one-group pre-test–post-test approach. A total of 30 participants were purposively selected from the working area of the Ranomuut Community Health Center, Manado City. The intervention included participatory education, demonstrations of local food processing, and assistance for families at risk of stunting. Knowledge was measured using questionnaires before and after the intervention and analyzed using a paired sample t-test. The results show that the mean knowledge score increased significantly from 71.67 ± 5.31 to 85.00 ± 5.72 (p < 0.001). The mean difference of 13.33 points with a large effect size (Cohen’s d = 1.87) indicates a strong practical impact of the intervention. Participants showed an increased understanding of stunting prevention and the ability to utilize local foods such as corn, sweet potatoes, moringa leaves, gedi leaves, and seafood as sources of nutrition for complementary feeding and toddler food. The conclusion is that empowerment-based interventions through education, demonstrations, and family assistance can increase families' knowledge about stunting prevention through the use of local Minahasa food ingredients. This approach has the potential to be replicated as a contextual and sustainable promotive-preventive strategy in supporting the acceleration of stunting reduction at the community level.